Web-Based Marketplace Program Design AT PT. Cipta Innovasi Teknologi Jakarta: Author's Country: Indonesia - Richky Faizal Amir; Andreyestha; eko pramono; Fajar Akbar (Information System; Universitas Buana Perjuangan Karawang, 2026)
Business processes in today's era are dynamic, including the sale of products and services. Websites or platforms such as marketplaces are one of the effective systems in running a company's business processes. Therefore, this research aims to design a web marketplace platform to make it easier for customers to find the right solutions for IT and services. The system's features function to manage various related data and information. When a customer needs a product or service, they will register, then begin searching for the appropriate solution, and then place an order. The author used Sketch to create the interface design on the website. The author used the waterfall approach in designing this system. The author also used the PHP programming language to design the website with the support of CodeIgniter version 4 as a framework to facilitate web design, and the use of HTML and CSS in the website's front-end design. The MySQL database is used for database system processing. With this research, it can produce a platform or website that makes it easier for customers to find the right IT solutions quickly.